Different types of organic matter in the reproduction test of the Californian earthworm Eisenia andrei (Research, Society and Development, 2020)
The present study aimed to evaluate the influence of different types of organic matter on reproductive toxicity of earthworms Eisenia andrei by means of Organization for Economic Cooperation and Development (OECD) Test No. 222 - Earthworm Reproduction Test. Seven different soil formulations with different sources of organic matter in different percentages were analyzed: Artificial Soil recommended by OECD with 10% and 5% organic matter (sphagnum); Tropical Artificial Soil with 10% and 5% organic matter (fiber coconut); Artificial Soil with Coffee + Mate 10% and 5%; and earthworm humus in treatments with and without boric acid (positive and negative control, respectively). The assays were performed with 5 replicates containing 10 adult earthworm Eisenia andrei. The boric acid concentration used was 281 mg.kg-1. OECD Artificial Soil with 10% organic matter had better performance (p < 0.05). Thus, it is concluded that for the conditions used in the study this is the best substrate for performing the reproductive performance test in Eisenia andrei, with sphagnum peat as a source of organic matter, in relation to the others tested.